Association between plasma Alzheimer's disease markers and MRI markers of cerebral small vessel disease and neurodegeneration: the SMART‐MR Study. (20th December 2022) - Twait, Emma L.; Gerritsen, Lotte; Moonen, Justine E.; Verberk, Inge M.W.; Teunissen, Charlotte E.; Visser, Pieter Jelle; van der Flier, Wiesje M.; Geerlings, Mirjam I.; ,
Abstract: Background: Biomarkers for Alzheimer's disease (AD), including amyloid‐beta (Abeta) and phosphorylated‐tau have recently been accurately detected in blood. Non‐specific biomarkers such as neurofilament light (NFL) and glial fibrillary acidic protein (GFAP) have been added as complementary biomarkers to fully investigate AD etiology in vivo. This has increased the possibility to examine relationships with other pathways to AD, such as white matter hyperintensities (WMH) and brain atrophy on MRI. Our aim was to explore the relationship between plasma AD biomarkers and MRI markers of cerebral small vessel disease and neurodegeneration in mid‐ and late life. Method: Data from 594 individuals (mean (SD) age: 64 (8) years; 17% female) were included from the SMART‐MR Study, a prospective cohort study of non‐demented individuals with a history of vascular disease from the UMC Utrecht in the Netherlands. MRI markers of CSVD included WMH, presence of infarcts, total brain volume (TBV), and hippocampal volume (HV) assessed on 1.5T MRI. AD plasma markers (Abeta1‐40, Abeta1‐42, pTau‐181, NFL, and GFAP) were assessed using Single Molecular Array (Simoa; Quanterix) assays. Linear regressions were performed for each plasma marker, as well as Abeta1‐42/Abeta1‐40 ratio, with age, sex, education, and intracranial volume, with WMH volume, TBV, and HV. Additionally, logistic regressions were performed for the presence of infarcts, including lacunar infarcts and cortical infarcts, corrected for age, sex, and education. Plasma AD levels were converted to z‐scores. P < 0.01 was considered statistically significant. Result: Higher NFL and pTau‐181 were associated with larger WMH volume (B NFL=0.17, 95% CI=0.06;0.29, p=0.003; B pTau‐181=0.16, 95% CI=0.06;0.26, p=0.001). Higher Abeta1‐40 (B=‐0.11, 95% CI=‐0.17;‐0.05, p<0.001) levels were associated with lower HV. Higher NFL (B=‐5.63, 95% CI=‐8.95;‐2.31, p<0.001) and Abeta1‐42 (B=‐3.61, 95% CI=‐6.26;‐0.96, p=0.008) were associated with lower TBV. Regarding infarcts, higher NFL was associated with any infarct (OR=1.42, 95% CI=1.13;1.78, p=0.003). Higher GFAP was marginally associated only with cortical infarcts (OR=1.45, 95% CI=1.09;1.92, p=0.01). Conclusion: Within non‐demented adults with a history vascular disease, plasma AD markers differentially mapped to MRI markers. NFL and pTau‐181 were associated with markers reflecting vascular damage, whereas amyloid markers were associated with atrophy in the TBV and HV.